Research on the Cutting Control Method of a Shield-Type Cutting Robot - Hongwei Ma; Limeng Xue; Chuanwei Wang; Wenda Cui (Actuators)
With problems of low cutting efficiency, poor forming quality, and low control accuracy in large-section semi-coal rock roadway tunneling, comprehensive coal tunneling seriously lags behind fully mechanized mining. A fuzzy PID control method was proposed, taking the cutting robot in a shield-type tunneling system as the research object. Using mathematical analysis and other methods, a kinematic model of the cutting robot was established, and the pose transformation matrix of the cutting robot during the cutting process was obtained. A limit model for the motion space of the cutting robot cutting drum was established, and the motion relationship between the driving cylinder and the cutting drum was obtained. A fuzzy PID cutting robot control scheme was designed. The feasibility of the model was validated by simulation methods, and the correctness of the model and simulation was verified through on-site experiments. The results indicate that the established cutting robot model is correct, and the proposed fuzzy PID control method for the cutting robot is feasible. The maximum error of the center control of the cutting drum was 5.5 mm, and the average date was 0.89 mm, which was far less than the standard of 50 mm for engineering of the cross-section cutting of the roadway. This study enriches the control theory of shield-type cutting robots by improving control accuracy, enhancing the cutting efficiency of large-section semi-coal rock tunnels, ensuring the quality of section forming, and narrowing the gap between comprehensive coal tunneling and fully mechanized mining.